Mobile Web 2.0: new spaces for learning - Coutinho, Clara Pereira (2011)
In this chapter, the author reflects on the emergence of Mobile Web 2.0, a new paradigm for learning in the 21st century, made possible by the combination of a powerful generation of mobile devices with Internet access and the Web 2.0 technologies that allow collaboration, participation, knowledge sharing and construction. The author presents the theoretical framework which sustains learning with mobile devices, and reflects on the potential of Mobile Web 2.0 for the development of informal learning and the construction of personal learning environments. Finally, the chapter presents educational scenarios for the development of mobile learning using Web 2.0 tools, in particular, those made possible using Twitter and m-Flickr.